Precise Torque Estimation in Interior Permanent Magnet Machines - Gundogan, Abdulkerim; Bakan, Ahmet Faruk (IEEE, 2018)
Interior permanent magnet synchronous machine (IPMSM) is preferred in many applications due to its advantages. It is quite important to reduce torque ripples in the applications where sensitivity is high, such as medical devices, defense industry, aviation and space technologies. In industry, torque estimation is generally implemented in an approximate manner and it is aimed to control the average value of the torque. If the torque value can be estimated precisely the torque ripples can be eliminated with control techniques. In this paper, an analytical model is proposed that can estimate the torque accurately. In the proposed analytical model, cogging torque, inductance, flux and flux harmonic components due to rotor angle are taken into account. Parameter changes were determined with the finite element program Maxwell model of the machine. The analytical model that includes the parameter changes of the machine is simulated by MATLAB / Simulink program and results are given comparatively.
Keywords: Torque control; precision torque estimation; IPMSM; torque fluctuation; variable machine parameters; PM SYNCHRONOUS MOTOR; RIPPLE MINIMIZATION; COGGING TORQUE; COMPENSATION; DESIGN; Engineering; Telecommunications